2017
DOI: 10.1111/acem.13252
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Following Possible Undiagnosed Aneurysmal Subarachnoid Hemorrhage: A Contemporary Analysis

Abstract: In a contemporary cohort of patients with aSAH, we observed no statistically significant increase in the adjusted odds of death or unfavorable neurologic outcomes among patients with clinical evaluations for possible aSAH-related symptoms in the 14 days preceding formal diagnosis of aSAH. While these findings cannot exclude a smaller risk difference than previously reported, they can help refine decision analyses and testing threshold determinations for patients with possible aSAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
2
3
0
Order By: Relevance
“…We also observed that 5% of SAH and 18% of bacterial meningitis cases were possibly misdiagnosed at index ED visits, estimates which are consistent with prior literature . Although we did not observe a significant change in the proportion of missed diagnoses over time, the small number of cases limited detection of differences.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We also observed that 5% of SAH and 18% of bacterial meningitis cases were possibly misdiagnosed at index ED visits, estimates which are consistent with prior literature . Although we did not observe a significant change in the proportion of missed diagnoses over time, the small number of cases limited detection of differences.…”
Section: Discussionsupporting
confidence: 90%
“…Nontraumatic subarachnoid hemorrhage (SAH) causes approximately 5% of acute-onset headaches in emergency department (ED) patients and has a 50% risk of serious disability or death at 1 year. 1 , 2 , 3 , 4 , 5 The first-line diagnostic test for SAH is noncontrast head computed tomography (CT), which is most sensitive within the first 6 hours of headache onset. 2 , 6 When CT is nondiagnostic and clinical suspicion remains high, lumbar puncture (LP) is the recommended second-line test (CT-LP approach).…”
Section: Introductionmentioning
confidence: 99%
“…5 Statistical models have suggested that, when using a threshold for disability in a delayed or missed SAH, CT/LP may not be costeffective. 26,27 Our results would refute this. If LP were to be abandoned, 6% patients with SAH would be missed causing significant harm.…”
Section: Abandoning Lpsupporting
confidence: 49%
“…The authors analyzed clinical course of patients finally diagnosed with SAH who through 14 days prior the diagnosis were examined due to suspicion of SAH with negative conclusion. They found that probable overlooking of SAH did not influence negatively their prognosis [16]. Chong et al reported similar observation as only 1.3% of patients with CT-negative SAH experienced further re-bleeding [15].…”
Section: Discussionmentioning
confidence: 87%